PENERAPAN MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN DARING UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI SISTEM PENCERNAAN - Noviyanti Indah Mawaddah; Martini Martini (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
The purpose of this study was to determine the implementation and effectiveness of the discovery learning model in improving learning outcomes on digestive system material. The subjects of this research were 26 students of class VIII-G SMPN 54 Surabaya. This research method is descriptive quantitative research design with one group pretest posttest design. The instruments used were pretest and posttest sheets each with 12 multiple choice questions and discovery learning implementation sheets. The results of the implementation of discovery learning obtained a very good category in 4 modes. The results of the homogeneity test state that the data are homogeneous with a significance level of 0.06. In the normality test, the data is normally distributed with a significance level of 0.39. The dependent t-test shows alpha 0.00 so that it is known that there is a significant difference between the pretest-posttest learning outcomes. The result of the implementation discovery learning is effective in improving learning outcomes on digestive system material.